A novel method for determining a newborn baby’s identity based on fingerprints - Lalović, Komlen G.; Tot, Ivan A.; Trikoš, Mladen B. (Vojnotehnički glasnik / Military Technical Courier, 2018)
This work presents a novel method for biometric identity verification for newborn babies in maternity wards based on fingerprint minutiae. The information system realized combines contemporary program languages such as: Java and Python as object-oriented languages, C programming language for device programming as structural (line) and SQL for storing encrypted data in a relational database management system. Also, there is the RSA asynchronous cryptographic algorithm as well as keys for storing the encrypted data of fingerprint minutiae. The information system implements a device for biometric verification of maternity i.e. a dual fingerprint scanner that provides data of mother’s and baby’s fingerprints at the very moment of childbirth and further guarantees maternity for each newborn baby with 100% accuracy, by generating a unique ID reference and encrypting these data with cancelable biometrics. This is a novel method for determining identity based on baby’s fingerprint minutiae.
Keywords: biometry; fingerprint; security; baby; method; information system